Model Development of Time and Cost Performance Measurement Methods - Earned Value Management (EVM) With a Combination of Dynamic Uncertainty Analysis (Case Study Road Construction Project in South Sulawesi Province) - THOENGSAL, JAMES (Kirana Publisher (KNPub), 2023)
In the execution cycle of a construction project often found a divergence varians especially withrespect to time and costs, which in detecting the occurrence of a deviation of the project is oftencarried out an evaluation of the performance of the results that have been achieved both on timeand cost. One method that is most frequently used in evaluating the performance of the cost andtime that the methods Earned Value Management (EVM), but in the study of analysis methods EVMcan be concluded that the assumptions used only linear and static the estimation of the time andcost of the project from performance has been generated just shows the estimated value of which isrigid and not dynamic, where as if the result of the estimated project cost and time performanceshows one possible course. Therefore, the purpose of writing this article which is to carry out adevelopment model of performance measurement time and cost of the project by analyzing acombination of uncertainty dymanic against time and cost of the project, which will be used incombination by entering the numbers uncertainties optimistic, enable / ideal and pessimism aboutthe estimated time performance and future costs at the time of the evaluation process is done(Freeze time). From the study results of the analysis conducted can be formulated basic equation inthe form of indicators that can be formulated to predict total project time and cost of the threeconditions, namely optimistic pessimist and ideal and analysis to the level of probability methodsnormal distribution to predict time and totalcost of completing a project construction